Análise do potencial do uso da energia solar em sistemas de bombeamento para irrigação no perímetro irrigado Piauí no município de Lagarto/SE - Leite, Douglas Vieira (2016)
The energy issue is a focus of important discussion today when the human activities are becoming increasingly dependent on resources that can supply the increased demand. From these problematics, it has been sought solutions in alternative energy sources, less impacting, which gradually tend to substitute conventional models toward a more diversified array. Solar energy becomes an option to consider in Brazil against the large existing potential, and the photovoltaic system of irrigation, one of the applications of photovoltaic systems. This paper proposes to study the potential use of solar energy in photovoltaic irrigation systems in Lagarto/SE. The study involves an estimated local solar radiation using the Angstrom- Prescott model by the determination of the equation coefficients and comparison between the estimated and actual values; the system design based on water demands of crops involved and cost compared to the conventional model. The results showed that for Lagarto/SE, the horizontal solar radiation can be estimated by the use of coefficients found in the monthly partition (coefficient a between 0.31 and 0.37 and b between 0.32 and 0.42) and insolation data (n). The estimated average annual solar radiation found in the region was 19.66 MJ/m²dia, with a minimum value of 14.45 MJ/m²dia in June and maximum of 23.94 M/ m²dia in November. The estimated solar radiation indices showed that the study area has a high potential for solar energy applications in general. The photovoltaic irrigation systems to supply the maximum water demand found in every 0.5 ha in systems of 5 to 60 m (head) are required installed photovoltaic modules of 310 Wp to 3.4 kWp. Compared to the conventional system, the photovoltaic is competitive in systems with head up to 30 m and their applicability varies with the source of water available.